"Pain talk": A triadic collaboration in which nurses promote opportunities for engaging children and their parents about managing children's pain. Issue 3 (9th August 2021) - Jordan, Abbie; Carter, Bernie; Vasileiou, Konstantina
Abstract: Effective communication with children about pain is important and has the potential to mediate the short‐ and longer‐term effects of pain on children. Most communication studies relating to children's pain have focused on language children use to describe everyday pain experiences. However, little is known regarding how health professionals, particularly nurses, communicate with children in healthcare settings about pain. This study aimed to explore how nurses talk to children and their parents about pain and what factors influence nurses' use of language and non‐verbal communication. A cross‐sectional mixed‐methods (predominantly qualitative) survey ("pain talk") was conducted, comprising qualitative items about pain communication and four vignettes portraying hypothetical cases of children representing typical child pain scenarios. Participants were recruited via email, social media, newsletters, established networks, and personal contacts. A total of 141 registered (68.1%) or in‐training nurses across 11 countries with experience of managing children's pain completed the survey. Textual survey responses were analyzed using conventional qualitative content analysis. Qualitative content analysis generated a meta‐theme "Being confident and knowing how to do 'pain talk'" and four main themes that described the functions, purpose, and delivery of "pain talk": (a) "contextualizing and assessing, " (b) "empowering, explaining, and educating, " (c) "supporting, affirming, and confirming, " and (d) "protecting, distracting, and restoring." "Pain talk" was a triadic collaborative communication process that required nurses to feel confident about their role and skills. This process involved nurses talking to children and parents about pain and creating engagement opportunities for children and parents. "Pain talk" aimed to promote the agency of the child and parent and their engagement in discussions and decision‐making, using information, support, and comfort. Nurses shaped their "pain talk" to the specific context of the child's pain, previous experiences, and current concerns to minimize potential distress and adverse effects and to promote optimal pain management. Abstract : Analyses of international qualitative survey data identified that nurses engage with 'pain‐talk' when talking to children and parents about child pain. This 'pain‐talk' focuses on emphasising the agency of the child and parent, taking account of the child's specific context and considering previous pain experiences to maximise effective pain management.